CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN - I Ketut Sunarwijaya; I Putu Edy Arizona (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Institutional share ownership can professionally monitor the progress of their investments so that the level of management control is so high that it can ultimately suppress the potential for fraud. While the effectiveness of the board of commissioners in balancing the strength of the CEO is strongly influenced by the level of independence of the board of commissioners. In addition, the Audit Committee has the authority to implement and certify investigations into issues within the scope of its responsibilities with the task of assisting the board of commissioners. This study uses corporate governance proxied with institutional ownership, independent commissioners, and audit committees as independent variables. The purpose of this study is to determine the effect of institutional ownership, independent commissioners, and audit committees on corporate value. This research is conducted in Indonesia Stock Exchange year 2013-2016. Determination of the sample using purposive sampling method to obtain 100 research samples. Data analysis used in this research is multiple linear regression analysis. The test results indicate that the variable of institutional ownership, independent commissioner, and audit committee have a positive effect on company value. This is indicated by the value of the regression coefficient and the significance level of each variable of 1.051 and 0.026; 0.078 and 0.035; and 0.076 and 0.033.